Analysis of the application of ventilative cooling in different regions of Turkey - Birturk, Asli; Yilmazoglu, M. Zeki (CLIMA 2022 conference, 2022)
Energy efficiency practices have gained momentum in recent years and continue to invest. The main motivation of this study is whether an effect can be achieved with ventilative cooling in terms of energy efficiency in buildings with mechanical ventilation, especially in transition seasons. In this context, the potential of ventilative cooling in different provinces of Turkey, where hourly average temperature values are taken, has been examined. According to the results obtained, ventilative cooling can be considered as an energy efficienct application.